The emotional geography of prison life. (February 2014) - Crewe, Ben; Warr, Jason; Bennett, Peter; Smith, Alan
Accounts of prison life consistently describe a culture of mutual mistrust, fear, aggression and barely submerged violence. Often too, they explain how prisoners adapt to this environment—in men's prisons, at least—by putting on emotional 'masks' or 'fronts' of masculine bravado which hide their vulnerabilities and deter the aggression of their peers. This article does not contest the truth of such descriptions, but argues that they provide a partial account of the prison's emotional world. Most importantly, for current purposes, they fail to describe the way in which prisons have a distinctive kind of emotional geography, with zones in which certain kinds of emotional feelings and displays are more or less acceptable. In this article, we argue that these 'emotion zones', which cannot be characterized either as 'frontstage' or 'backstage' domains, enable the display of a wider range of feelings than elsewhere in the prison. Their existence represents a challenge to depictions of prisons as environments that are unwaveringly sterile, unfailingly aggressive or emotionally undifferentiated.